Sistem Pendukung Keputusan Penentuan Dosen Pembimbing Tugas Akhir Menggunakan Fuzzy Dan Simple Additive Weighting Berbasis Android: Studi Kasus IKADO Surabaya - Titasari Rahmawati; Alexander Wirapraja; Ester Cavarius Soesilo (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2022)
Final Project is a scientific work carried out by conducting research based on a problem and supported by data obtained from research activities. In the process of completing the final project, students are usually guided by a supervisor. Currently, students at IKADO Surabaya choose their supervisor only by subjective assessment and only through intuition. This causes the supervisors chosen by students to be less relevant to the topic of the final project and also in terms of experience in guiding with the topic of the final project is still small so that it affects the results/ quality of the final project itself. Therefore, we need an application that can provide recommendations to students regarding their final assignment supervisor in accordance with certain criteria. In this study, the application developed will use the fuzzy method and simple additive weighting to get the supervisor's recommendation according to the topic of the student's final project. The results show the choice of the names of the first and second supervisors, along with the top five ranking lecturers' names that can be used as alternative supervisors. The development method used is extreme programming, and uses testing in the form of Blackbox testing, while testing the ease and usability of the application uses usability testing. By making a decision support application called SIPEKA, it can help students and final project coordinators in determining alternative final project supervisors, by utilizing the features contained in the application.